Sustainable intensification is the answer to global food insecurity (sir gordon conway) - Conway, Gordon (2016)
Presentation by Sir Gordon Conway, professor of international development at Imperial College, London and former president of the Rockefeller Foundation IFPRI, in collaboration with the USAID Alumni Association, hosted this special event where Sir Gordon Conway emphasized that sustainable intensification offers a practical pathway towards the goal of producing more food while ensuring that the natural resource base, on which agriculture depends, is sustained and improved for future generations. He explored Sustainable Intensification through three mutually reinforcing pillars – Ecological Intensification, Genetic Intensification, and Socio-Economic Intensification.